Socialization of 4C and HOTS Based Learning Device for Science Teachers in Paloh - Masriani Masriani; Hairida Hairida; Eny Enawaty (JPKM (Jurnal Pengabdian Kepada Masyarakat) UNTAN, 2021)
One of the important things in implementing 2013 curriculum is integrating 21st-century learning tools and applying them in classroom learning. Therefore, teachers are required to master 21st-century skills properly. The teacher's learning tools must refer to the mastery of 21st-century skills, namely 4C and HOTS. In general, teachers arrange learning tools based on their perceptions, not adjusting the curriculum's demands. Based on this, the socialization of 4C and HOTS-based learning tools was carried out to junior and senior high school science teachers in Paloh. The method used was lectures, discussions and tutorials on making 4C and HOTS-based learning device. Evaluation through filling out questionnaires was carried out after the socialization had been carried out. The observations indicated that the participants gave positive responses to the socialization that was carried out. It was evidenced by very high listening activity and enthusiasm for asking questions. It was supported by a questionnaire where 85% of participants stated that this activity was beneficial.